2021
DOI: 10.3390/ma14175062
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aging Treatment on Corrosion Behavior of a Tensile Deformed Al-Cu-Mn-Fe-Zr Alloy in 3.5% NaCl Solution

Abstract: In this paper, the effects of an aging treatment on the corrosion resistance/mechanism of a tensile deformed Al-Cu-Mn-Fe-Zr alloy are investigated. The impedance magnitude and polarization resistance increase, while the corrosion current decreases with the increased aging time and temperature. The discontinuously-distributed precipitates and precipitation-free zone, which can cut the corrosion channels, appear at grain boundaries when the temperature is relatively high and the aging time is relatively long. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…For the characteristic of the poor passive layer, the localized attacks began to diffuse after a time, so high energy was presented at low frequencies indicating pitting diffusion. Other authors such as Lin et al [ 72 , 73 ] commented that in order to improve the corrosion resistance of light alloys it is important to consider the effect of precipitate pretreatments on the microstructure, seeking to ensure that they are well distributed. The concentration of precipitates of Cu, Zn, or Mg can cause cracks or failures in the alloys, and this was reflected in the transients of the electrochemical noise-generating drops in potential and increase in the current [ 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the characteristic of the poor passive layer, the localized attacks began to diffuse after a time, so high energy was presented at low frequencies indicating pitting diffusion. Other authors such as Lin et al [ 72 , 73 ] commented that in order to improve the corrosion resistance of light alloys it is important to consider the effect of precipitate pretreatments on the microstructure, seeking to ensure that they are well distributed. The concentration of precipitates of Cu, Zn, or Mg can cause cracks or failures in the alloys, and this was reflected in the transients of the electrochemical noise-generating drops in potential and increase in the current [ 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of precipitates at the grain boundaries of GBPs in the material microstructure resulted in a large potential difference between the anodic grain boundary and its cathodic center. It is suggested that as the aging stage deepened, alloy segregation occurred, leading to an increase in the copper content of GBPs as a result of the η phase moving toward equilibrium content [2,12,18,41,44]. The size, spacing, and copper content of GBPs after RRA treatment increased as the aging step deepened, which is beneficial for the grain boundary to resist anodic dissolution [43].…”
Section: Corrosion Resistance Testsmentioning
confidence: 99%
“…This reduces the driving force for local corrosion and contributes to improved resistance to intergranular corrosion [43]. At the same time, grain centers become susceptible to dissolution [44]. In the RRA state, the MPs precipitates are also enriched in copper, which further promotes the reduction of copper content in the matrix [47].…”
Section: Corrosion Resistance Testsmentioning
confidence: 99%
See 1 more Smart Citation